Enhancement of X-ray emission from nanocolloidal gold suspensions under double-pulse excitation - Wei-Hung Hsu (Beilstein Journal of Nanotechnology, 2018)
Enhancement of X-ray emission was observed from a micro-jet of a nano-colloidal gold suspension in air under double-pulse excitation of ultrashort (40 fs) near-IR laser pulses. Temporal and spatial overlaps between the pre-pulse and the main pulse were optimized for the highest X-ray emission. The maximum X-ray intensity was obtained at a 1–7 ns delay of the main pulse irradiation after the pre-pulse irradiation with the micro-jet position shifted along the laser beam propagation. It was revealed that the volume around gold nanoparticles where the permittivity is near zero, ε ≈ 0, accounts for the strongest absorption, which leads to the effective enhancements of X-ray emission.